Synergistic reduction of copper (II) and oxidation of norfloxacin over a novel sewage sludge-derived char-based catalyst: Performance, fate and mechanism. (1st May 2018) - Liu, Jin-Jun; Diao, Zeng-Hui; Liu, Cui-Mei; Jiang, Dan; Kong, Ling-Jun; Xu, Xiang-Rong
Abstract: Nowadays, clean-up of waters with coexisting heavy metal ions and organic pollutants is of great environmental importance. In this study, a novel sewage sludge-derived char-based catalyst was firstly synthesized, and coupled with hydrogen peroxide for the simultaneous removal of copper (II) and norfloxacin in aqueous solutions. The most relevant findings revealed that zero-valent iron and zero-valent aluminum particles were successfully formed on the catalyst surface when the leaching of the sludge-derived char was reduced by the green tea extract. Nearly 100% of both copper (II) and norfloxacin were simultaneously removed due to a synergistic effect between the reduction of copper (II) and the oxidation of norfloxacin over the catalyst. The gradual addition mode of hydrogen peroxide exhibited a better performance on the simultaneous removal of copper (II) and norfloxacin. The coexisting anions like nitrate and phosphate had significant negative effects on the copper (II) removal, whereas carbonate, fluoride and phosphate had significant negative effects on the norfloxacin removal. Different copper species like zero-valent copper, copper oxide and copper hydroxide were identified in copper (II) reduction process, whereas a total of eight oxidative products were identified in norfloxacin oxidation process. A possible reaction mechanism for the simultaneous removal of copper (II) and norfloxacin by the sewage sludge-derived char-based catalyst/hydrogen peroxide system was proposed. The adsorption of both copper (II) and norfloxacin over the catalyst were firstly occurred, and then the reduction of copper (II) over both zero-valent iron and zero-valent aluminum particles on the catalyst surface as well as the Fenton oxidation of norfloxacin were followed. Graphical abstract: Image 1 Highlights: A novel sewage sludge-derived char-based catalyst was firstly synthesized. A synergistic effect between reduction of Cu 2+ and oxidation of NOR was achieved. The gradual addition mode of H2 O2 could remarkably enhance NOR oxidation. The intermediate products of both Cu 2+ and NOR were identified. A mechanism for the simultaneous removal of Cu 2+ and NOR was proposed.